Numerical determination of fluid‐to‐particle mass and heat transfer coefficients in packed bed reactors. Issue 5 (19th December 2022) - Weng, Junqi; Zhang, Qunfeng; Yu, Jiahao; Yu, Qihuan; Ye, Guanghua; Zhou, Xinggui; Yuan, Weikang
Abstract: A method based on particle‐resolved CFD is built and validated, to calculate the fluid‐to‐particle mass and heat transfer coefficients in packed beds of spheres with different tube‐to‐particle diameter ratios ( N ) and of various particle shapes with N  = 5.23. This method is characterized by considering axial dispersion. The mass and heat transfer coefficients increase by 5%–57% and 9%–63% after considering axial dispersion, indicating axial dispersion should be included in the method. The mass and heat transfer coefficients are reduced as N decreases. The catalyst particles without inner holes show higher mass and heat transfer coefficients than the ones with inner holes, because of unfavorable fluid flow in inner holes. The bed of trilobes has the highest mass and heat transfer coefficients, being 85% and 95% higher than the one of spheres. This work provides a versatile method and some useful guidance for the design of packed bed reactors.